Persistent metabolic syndrome and risk of cardiovascular disease in children and adolescents - Camilla Ribeiro Lima de Farias; Carla Campos Muniz Medeiros; Diogo Rodrigues Souza; Ivelise Fhrideraid Alves Furtado da Costa; Mônica Oliveira da Silva Simões; Danielle Franklin de Carvalho
ABSTRACT Objective: to verify persistence of metabolic syndrome (MetS) and components in overweight children and adolescents, as well as its relation to socioeconomic and demographic characteristics and to the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) score. Method: a two-point longitudinal study: at enrollment and after a 24-month interval, with 133 individuals ages from two to 18 years. The demographic anthropomorphic and blood variables were evaluated. Analysis was carried out by simple and paired association tests, as well as multiple logistic regression. Results: persistent MetS was observed in 38.3% of the sample, associated cardiovascular risk (ACR) in 79.7%, reduction in arterial pressure and do HDL-c. After adjusting for age and sex, excess weight (ExpB: 0.182; CI: 0.059-0.561), low HDL-c (ExpB: 9.247; CI: 1.157-73.930) and high LDL-c (ExpB:1.915; CI: 0.921-3.979) were associated with persistent MetS. Conclusion: persistent MetS was associated with obesity, HDL-c and LDL-c, but not with the PDAY score.